2021 IEEE Winter Conference on Applications of Computer Vision (WACV) 2021
DOI: 10.1109/wacv48630.2021.00047
|View full text |Cite
|
Sign up to set email alerts
|

SWAG: Superpixels Weighted by Average Gradients for Explanations of CNNs

Abstract: Providing an explanation of the operation of CNNs that is both accurate and interpretable is becoming essential in fields like medical image analysis, surveillance, and autonomous driving. In these areas, it is important to have confidence that the CNN is working as expected and explanations from saliency maps provide an efficient way of doing this. In this paper, we propose a pair of complementary contributions that improve upon the state of the art for region-based explanations in both accuracy and utility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Recently, a set of techniques have been introduced that aim to pool the individual pixel scores given by gradientbased techniques into more interpretable regions. These are XRAI [13] and SWAG [10]. Both have a similar approach in that they generate superpixels using the input image, and then assign a score to these regions based on the gradient values that lie within them.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a set of techniques have been introduced that aim to pool the individual pixel scores given by gradientbased techniques into more interpretable regions. These are XRAI [13] and SWAG [10]. Both have a similar approach in that they generate superpixels using the input image, and then assign a score to these regions based on the gradient values that lie within them.…”
Section: Related Workmentioning
confidence: 99%
“…However, assigning a score for individual pixels often has the appearance of noise and has been deemed to be less interpretable than methods which score larger regions [13,29,30]. Recently techniques have been introduced that pool these individual pixel scores into more interpretable regions [10,13]. Of these, Superpixels Weighted by Average Gradient (SWAG) [10], is able to produce explanations efficiently using only a single forward and backward pass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the separation of the information from Grad-CAM into spatial and temporal information works effectively for a more detailed explanation [13]. SWAG-V [12] enhances the framework SWAG [11] by averaging and smoothing a saliency map at the super-pixel level.…”
Section: Extensions For 3d-cnn Predictionsmentioning
confidence: 99%
“…The quality of heatmaps has been measured by how much the heatmaps improve ILSVRC localization (Zhou et al, 2016;Selvaraju et al, 2016). Metrics have been designed to measure changes after the manipulation of pixels with high relevance according to the XAI methods used (Bach et al, 2015;Samek et al, 2017;Hooker et al, 2019;Hartley et al, 2021), one of which, the most relevant first (MoRF) will be adopted here. We also use weight randomization sanity check in (Adebayo et al, 2018), where similarity is measured between explanations given before and after layer weight modification, for example, using rank correlation.…”
Section: Related Workmentioning
confidence: 99%